AMPERE (Asset Mapping Platform for Emerging CountRies Electrification) a GNSS-based integrated platform for energy decision makers (GEOmedia, 2021)
The purpose of the AMPERE (Asset Mapping Platform for EmergingcountRies Electrification) project is to provide a dedicated solution forelectrical power network information gathering: AMPERE will supportdecision making actors (e.g. institutions and public/ private companiesin charge to manage electrical network) to collect all needed info toplan electrical network maintenance and upgrade. AMPERE solutionis based on a GIS Cloud mapping technology, collecting on field dataacquired with optical/thermal cameras and LIDAR installed on board aRemote Piloted Aircraft (RPA).AMPERE project has received funding from the European GNSSAgency (grant agreement No 870227) under the European Union'sHorizon 2020 research and innovation programme.